Season, age, sex, and location impact the density of tooth rake mark and dorsal fin notch of Indo‐Pacific humpback dolphins (Sousa chinensis) in the northern South China Sea. Issue 2 (9th November 2022) - Serres, Agathe; Lin, Wenzhi; Liu, Binshuai; Lin, Mingli; Liu, Mingming; Chen, Shenglan; Li, Songhai
Abstract: Tooth rake marks are usually used as an indicator of received aggression in odontocetes whose social interactions are difficult to observe directly. Photographic data from five locations of the northern South China Sea were used to analyze seasonal, demographic, and geographic effects on the density of tooth rake marks and dorsal fin notches in Indo‐Pacific humpback dolphins ( Sousa chinensis, IPHDs). The analysis revealed that fresh tooth rake marks were most frequent during the dry season. Males exhibited significantly higher rake mark density than females and rake density declined significantly with age. The density of notches was also significantly higher for males than for females, and lower for young dolphins than for mid‐aged and adult ones. Geographically, tooth rake mark and notch density were the highest in Sanniang Bay and Southwestern Hainan. These results provide indirect evidence of variation in social interactions across seasons, across the lifespan of an individual, between sexes, and among different locations. This variation may result from changes in biological parameters, differences in social lives, and habitat characteristics. A model to determine the sex of dolphins was tested, and after further validation, such sex assignment could contribute to understanding IPHDs' social structure.